Problem of Social Leadership and Social Conflict in USSR in Works of Scientists of Russian Emigre of 1950s and 1970s - T. M. Dimoni (Научный диалог, 2020)
The issue of understanding by scientists and public figures of the Russian Emigre of social relations in the USSR of the 1950-1970s is considered in the article. The novelty of the work lies in the choice of sources of research - articles and books of figures of Russian Emigre. The author emphasizes that the main part of the ideas of the considered authors is not sufficiently represented in the scientific community. It is noted that the founders of the research of Soviet society were scientists from the Munich Institute for the Study of History and Culture of the USSR, which in 1957 held a major international conference “Modern Soviet Society”. It is concluded that the conference reports on the multiplicity of Soviet society, the presence of serious legal and economic differentiation, the emergence of new progressive classes (engineering and technical intelligentsia) laid the foundation for promoting research on Russian society. According to the author, in the late 1960s, this direction was actively cultivated by Soviet dissidents who emigrated to the West, and close associates who remained in the USSR (A. A. Amalrik, K. Bourzhuademov, S. S. Malevsky-Malevich, V. Belotserkovsky). A review of the historiography of the Russian Emigre allows us to create a platform for reflection on the social forces of Soviet society, the driving motives of their activity and the struggle for a place in the class hierarchy.